The Structure and Mechanical Characteristics of the Hypereutectic Silumin (Al-22-24 wt.% Si), Irradiated by a Pulsed Electron Beam; Energy Fluxes and Radiation Effects (EFRE-2020 online) - Petrikova E. Elizaveta; Ivanov Yu. F. Yuriy Fedorovich; Rygina M. Maria; Prudnicov A. Alexander; Teresov A. Anton; Vorobjev (Vorobyov) M. S. Maksim Sergeevich (2020, 2020)
Title screen